Fuzzy set approach to hyperideal theory of po-ternary semihypergroups. (3rd April 2019) - Talee, Aakif Fairooze; Abbasi, Mohammad Yahya; Khan, Sabahat Ali; Hila, Kostaq
Abstract: The aim of this paper is to apply fuzzy sets in hyperstructure theory. We initiate fuzzy hyperideals over po-ternary semihypergroups and explore some related properties. We introduce the concept of po-fuzzy point in po-ternary semihypergroups. Moreover, we give a number of characterizations for regular po-ternary semihypergroups by using the concept of fuzzy hyperideals.